2020
DOI: 10.1038/s41598-020-60222-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing vehicle passenger fatality have changed over 10 years: a nationwide hospital-based study

Abstract: Traffic injury trends have changed with safety developments. To establish effective preventive measures against traffic fatalities, the factors influencing fatalities must be understood. The present study evaluated data from a national medical database to determine the changes in these factors over time, as this has not been previously investigated. This observational study retrospectively analysed data from the Japanese Trauma Data Bank. Vehicle passengers involved in collisions from 2004-2008 and 2016-2017 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
5
4
1
Order By: Relevance
“…With regard to vital signs in passengers, our results suggest that a lower BT was significantly associated with the fatality rate. This finding is similar to that found in adults who were examined between 2004 and 2008 [5]. Therefore, measuring BT in patients would be useful for estimating the prognosis.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…With regard to vital signs in passengers, our results suggest that a lower BT was significantly associated with the fatality rate. This finding is similar to that found in adults who were examined between 2004 and 2008 [5]. Therefore, measuring BT in patients would be useful for estimating the prognosis.…”
Section: Discussionsupporting
confidence: 86%
“…This difference between studies is likely because of the difference in the distribution of the seating position between children and adults. Most child passengers sat in the rear seat in the present study, whereas more than three-quarters of adult vehicle passengers sat in the driver's seat in the previous study [5].…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…This fact is substantially due to seatbelt-induced abdominal injuries. A recent study based on nationwide hospital data suggested that the AIS score of the abdomen was the single signi cant in uencing factor for fatalities of motor vehicle passengers [19]. The authors also suggested that seatbelt compression might somewhat contribute to the occurrence of abdominal organ injuries.…”
Section: Discussionmentioning
confidence: 99%